(3TQM GdTGajIs - (3GdfXGe MSf Hf eMehO GdfjSCHhQis; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3hHYO abO GdJeS efi ebOeI ai GdJUQja s
(3BNQgG (B:s
(3hMJi dchfg HeYfi Edi bGd GdeaJbQ Edi Yah QHg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas